Democracy in contemporary Arab Islamic thought from rejection to correction - bourasse, youcef (Journal of Social Sciences and Humanities, 2021)
After democracy was approved by the Islamic trend in the nineteenth century, criticism came, either by rejection by a stream of it or by amendment by another, the first in the sense of disbelief, and the second on the grounds that its applications contradict its theoretical example. The aim of this essay is mainly to know the position of the Islamic intellectual trend with its different currents towards democracy, the content of its criticism of it, and its alternatives on the subject. In order to reach this goal, we used the method of analysis to find out his arguments on the subject. As for the results obtained, we can talk about the power of criticism presented by the Islamic trend, from both the rejectionist and corrective sides, of Western democracy on the theoretical level, and reaching a kind of procedural democracy.